SIMPLE ELECTROSPINNING ASSEMBLY FOR THE PREPARATION OF POLYVINYL ALCOHOL NANOFIBERS CONTAINING PIPER BETLE (L) - WIRAHADIKESUMA, IKHWAN; MANALU, WASMEN; MAHESWARI, HERA; MADDU, AKHIRUDDIN; ALMIAHSARI, ASHRI; RIZKI, MUHAMMAD; FITRIANA, MIA (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this research was to assemble an electrospinning device with some components from used medical devices in hospital, so that it could be utilized to produce nanofibers containing Piper betle (L). Methods: The electrospinning was assembled with the main components were the 20 kV high voltage (hV) power supply (module), the Terumo TE-331 syringe pump and the collector. The resulting device was then evaluated for tool performance. The device was used to produce Polyvinyl Alcohol (PVA)-based nanofibers with Piper betle (L) as the active ingredient. The nanofibers produced were then tested for antibacterial activity, morphology by Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Results: The polymer solution was pushed by a syringe pump with a flow rate of 15 ml/h into the spinneret. In this electrospinning process, the formed nanofibers appear visually as a thin layer on the collector. With variation in PVA concentration and the same concentration of Piper betle l. as the active ingredient, the results showed that the nanofiber carrier did not affect the efficacy provided by Piper betle (L). The characterization with SEM revealed that the assembled tool was able to make nanofiber preparations that have fine continuous/fairly regular fibers with an average diameter of 46.479±2.406 nm. Meanwhile, the analysis using FTIR showed the presence of OH stretching groups of phenolic compounds from Piper betle (L). Conclusion: It can be concluded that the electrospinning was successfully assembled from unused medical devices in hospital and proven to produce nanofibers.